Non-violent drug users should face no penalty—a call from the Global Commission on Drug Policy. (14th November 2016) - Dreifuss, Ruth; Bém, Pavel
Abstract : We urgently need pragmatic reform to develop effective and humane drug policies, including regulated drug markets, because prohibition has failed, write Ruth Dreifuss and Pavel Bém